El apego y desarrollo emocional en los niños de educación inicial - Quila Guishca, Paola Fernanda (2020)
The present project has as its research theme "Attachment and emotional development in children of Initial Education" with the objective of diagnosing the incidence of attachment and emotional development in children of "Manuel Gonzalo Albán Rumazo" Educational Unit, located in Alaquez Parish Latacunga Canton. For the collection of information, the methodological approach was mixed, qualitative using the observation technique (as a tool the observation card) and quantitative (using the survey technique and the interview). It has as a tool the questionnaire directed to the parents and teachers of the Educational Unit, besides it is of applied type, descriptive, with a documentary design and of field; with the purpose of carrying out the process in an orderly manner, allowing us to reach the reality of the research, through the tabulation and interpretation of it. As far as the theoretical review is concerned, it can be determined that attachment is the affective bond that is consolidated from birth, since the first attachment bond is the mother, in whom she will feel safe and protected before any threat, later on, as she grows up, she will bond with third parties (parents, siblings), which will favor the development of stable emotions, such as empathy, self-image, self-control, selfesteem, thanks to the proximity with the parents, which will provide affection and communication, this will depend on the style of upbringing that they apply, in the case of applying an inadequate upbringing it is probable that the children acquire an insecure attachment, showing negative emotions, such as anxiety, insecurity, shyness, low tolerance to frustration, difficulty of socialization, in the worst case aggression because of impulsivity. It was determined that other factors also influence, such as the infant's personality, physical or emotional abandonment and attachment, which is the difficulty of becoming familiar with the baby, all of which will later cause difficulties in the physical and psychological functions, which involves the teaching-learning process of the child.